O processo de criação da dramaturgia no cinema industrial mestiço – o caso de Juan José Campanella - Almeida, Gabriela Sandes Borges de (2016)
This research aims to map the complexity of the dramaturgical’s creation process at the Juan José Campanella cinema. In this direction, his feature film The secret in their eyes – El secreto de sus ojos, co-written and directed by him, will be analyzed. The material of analisys, or documents of the process, will be: 1. different script versions; 2. decoupage of the final cut; 3. contents of the "extras" section at the commercial DVD; and 4. interviews and statements given by the author to the media in general and to the researcher, as well as members of the film artist crew. The methodology to be used is the Creation Process Criticism (Cecilia Almeida Salles), related to the study of the creative process, in which approach it is discussed as a network in permanent construction (second Pierre Musso's concept of network). In theoretical terms, the research’s approach will be transdisciplinary and based on the Semiotic of Culture, in dialog with the fields of Film Theory (David Bordwell, Ismail Xavier, Jean-Claude Carrière), Filmic Dramaturgy (Robert Mckee, Yves Lavandier, Syd Field, David Mamet) and the Cultural Métissage (François Laplantine, Serge Gruzinski, Jesús Martín-Barbero, Néstor Canclini and Amálio Pinheiro)